Kaale Belongings and Evangelical Becomings : An ethnography of Finnish Roma - Roman, Raluca Bianca, (Roma History and Culture ;, 2025)
By looking at the national Roma community in Finland, the Finnish Kaale, this book explores the impact of Evangelical Christianity on social and political mobilisation, and the ways in which religious identity becomes entangled with community identity. Based on extensive fieldwork carried out over the course of a decade, and coupled with archival research into the social mobilisation of Roma in Finland since the 20th century, this book presents an ethnographic picture of the ways in which members of the national Roma community in Finland live with, engage with and embody their religious outlook, offering a unique perspective on the role of Christianity within the lives of Roma communities in Europe.